Strategi pemanfaatan limbah bathok kelapa masyarakat Sidomulyo Dusun Kalimeneng Kabupaten Blitar - Ubaidillah, Ubaidillah; Sapitri, Neli Ana (Penamas: Journal of Community Service, 2021)
Sidomulyo is the main coconut supplier village of Blitar City. There is a problem; the coconut shell waste is only used for fuel or becomes trash. Then, it appeared the puddle that becomes the mosquito lair. It could attack community health. Based on that problem, there is an effort to utilize the coconut shell waste through a cooperation scheme together with creative and home industries entrepreneurs. The methods used were: field-observation, collected data, socialization, up to assistance related to the utilization of coconut shell waste. It was conducted for the traditional markets up to micro small and medium enterprises or UMKM. The results of this study were increasing the communities' income. The second, creating the community of coconut shell waste collectors, then the third is to build cooperation together with the entrepreneur and a clean environment without the mosquito.